A STUDY ON DETERMINANT FACTORS INFLUENCING PURCHASE DECISIONS OF BELIKOPI THROUGH ONLINE FOOD DELIVERY APPLICATIONS - Rahmadanty, Rifadia Shinta; Asteria, Beta (SEGMEN: Jurnal Manajemen dan Bisnis, 2026)
Consumers’ purchase decisions are examined in this study by focusing on the roles of pricing, product quality, brand image, and technology acceptance on consumer buying choices of Belikopi through online food delivery applications in Yogyakarta. The fierce rivalry among coffee businesses operating on digital channels necessitates thorough insight into the elements that influence consumer purchasing actions.This investigation utilized a quantitative methodology conducted via a survey method. The relationships between the variables were statistically tested using a multiple linear regression approach.. Pricing, product quality, and brand image are found to possess a significant influence on buying decisions, while technology acceptance does not demonstrate a significant effect. Product quality is identified as the most influential variable determining consumer purchase decisions